Constructing Cassandra : reframing intelligence failure at the CIA, 1947-2001 - Jones, Milo, 1967-; Silberzahn, Philippe (Stanford University Press, 2013)
The CIA was created in 1947 in large part to prevent another Pearl Harbor. On at least four dramatic occasions, the Agency failed at this task. There has been no shortage of studies to understand how such failures happened. Until now, however, none of the explanations proffered has been fully satisfying, and sometimes competing explanations have been mutually incompatible. In contrast, this book proposes a unified, coherent and rigorous theory of intelligence failure built on culture and identity.
Keywords: United States. -- Central Intelligence Agency -- History.; United States. -- Central Intelligence Agency; Intelligence service -- United States -- History.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; POLITICAL SCIENCE / Political Freedom; Intelligence service; United States; History